Pickle and Chutney Development from Fresh Hog Plum (Spondias dulcis) (Journal of Environmental Science and Natural Resources, 2013)
The experiment was conducted to develop pickle and chutney from fresh hog plum fruit. The pickle was made with 5%, 10%, 15% and 20% salt concentration. The chutneys were made with 25%, 30%, 35% and 40% sugar concentration. Among them, the best pickle and chutney was identified on the basis of overall acceptability. The study showed that the color, flavor, texture and overall acceptability of different pickles and the chutneys were different. The pickle (P15) made with 15% salt and the chutney (C40) made with 40% sugar concentration was best among others of the similar product. Higher concentration of sugar and salt gives higher acceptability for chutney and pickle, respectively. Among different changes in chemical composition, moisture and vitamin C concentration were prominent during preparation of pickle and chutney. The moisture content was 59.69% and 43.08% for pickle and chutney respectively which were nearly two third to half of the initial concentration of fresh hog plum fruit. The storage stability was studied for both the products and it is seen that chutney (4 month) was lower than storage stability of pickle (5 month).DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14604 J. Environ. Sci. & Natural Resources, 5(2): 67-72 2012